2009
DOI: 10.1080/17522430802654105
|View full text |Cite
|
Sign up to set email alerts
|

Are social phobia and paranoia related, and which comes first?

Abstract: To cite this Article Rietdijk, J. , van Os, J. , Graaf, R. de , Delespaul, Ph. and Gaag, M. van der(2009) Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
7
11
0
Order By: Relevance
“…The present general population study found a nonrandom co-occurrence of social phobia and paranoid symptoms, which is in accordance with the high rates of social phobia reported in patients with a diagnosis of schizophrenia (94)(95)(96) and with associations between social anxiety and paranoid thinking previously found in clinical (1-3) and epidemiological studies (59). Moreover, the present results consistently showed that paranoid symptoms were associated with social phobia both at the DSM-IV criterion level and at the symptomatic level, whereas other delusions did not show such associations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present general population study found a nonrandom co-occurrence of social phobia and paranoid symptoms, which is in accordance with the high rates of social phobia reported in patients with a diagnosis of schizophrenia (94)(95)(96) and with associations between social anxiety and paranoid thinking previously found in clinical (1-3) and epidemiological studies (59). Moreover, the present results consistently showed that paranoid symptoms were associated with social phobia both at the DSM-IV criterion level and at the symptomatic level, whereas other delusions did not show such associations.…”
Section: Discussionsupporting
confidence: 92%
“…Social anxiety, on the other hand, has been found to be correlated with feeling hostile towards others, and with hostile perceptions of others (97). Furthermore, the study confirmed the prospective association between paranoid symptoms and later onset of social phobia, as previously reported in the NEMESIS study (59). Furthermore, the study confirmed the prospective association between paranoid symptoms and later onset of social phobia, as previously reported in the NEMESIS study (59).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Social anxiety is an interesting comparison because it has a number features in common with paranoid delusions, such as selective attention to and overestimation of threat in social situations (Birchwood et al, 2006;Hirsch & Clark, 2004) and the tendency to perceive oneself as the centre of peoples' attention and to be judged negatively by others. In the light of these similarities and the rather substantial correlation of symptom scores of social anxiety and paranoid ideation (Gilbert, Boxall, Cheung, & Irons, 2005;Rietdijk, van Os, De Graaf, Delespaul, & van der Gaag, 2009) the absence of an association of social anxiety and JTC clearly seems to support the assumption that the JTC-bias is delusion specific and not largely explicable by anxiety. The lack of impact of trait-anxiety is also confirmed by other studies that found no indication of JTC in patients with panic disorder (Fraser et al, 2006), anxiety problems (Brankovic & Paunovic, 1999) or patients with OCD who even tended towards more cautious decisions (Fear & Healy, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…This would suggest that social anxiety would be a valuable treatment target (Rietdijk, van Os, de Graaf, Delespaul & van der Gaag, 2009), and there is evidence that CBT is a highly effective treatment of social phobia (Clark et al, 2006).…”
Section: A Critical Analysis Of the Fep Studies: 2 Theoretical Undermentioning
confidence: 99%